3D Melt-Extrusion Printing of Medium Chain Length Polyhydroxyalkanoates and Their Application as Antibiotic-Free Antibacterial Scaffolds for Bone Regeneration - Marcello, Elena; Nigmatullin, Rinat; Basnett, Pooja; Maqbool, Muhammad; Prieto, M. Auxiliadora; Knowles, Jonathan C.; Boccaccini, Aldo R.; Roy, Ipsita (ACS Biomaterials Science and Engineering, 2024)
In this work, we investigated, for the first time, the possibility of developing scaffolds for bone tissue engineering through three-dimensional (3D) melt-extrusion printing of medium chain length polyhydroxyalkanoate (mcl-PHA) (i.e., poly(3-hydroxyoctanoate-co-hydroxydecanoate-co-hydroxydodecanoate), P(3HO-co-3HD-co-3HDD)). The process parameters were successfully optimized to produce well-defined and reproducible 3D P(3HO-co-3HD-co-3HDD) scaffolds, showing high cell viability (100%) toward both undifferentiated and differentiated MC3T3-E1 cells. To introduce antibacterial features in the developed scaffolds, two strategies were investigated. For the first strategy, P(3HO-co-3HD-co-3HDD) was combined with PHAs containing thioester groups in their side chains (i.e., PHACOS), inherently antibacterial PHAs. The 3D blend scaffolds were able to induce a 70% reduction of Staphylococcus aureus 6538P cells by direct contact testing, confirming their antibacterial properties. Additionally, the scaffolds were able to support the growth of MC3T3-E1 cells, showing the potential for bone regeneration. For the second strategy, composite materials were produced by the combination of P(3HO-co-3HD-co-HDD) with a novel antibacterial hydroxyapatite doped with selenium and strontium ions (Se-Sr-HA). The composite material with 10 wt % Se-Sr-HA as a filler showed high antibacterial activity against both Gram-positive (S. aureus 6538P) and Gram-negative bacteria (Escherichia coli 8739), through a dual mechanism: by direct contact (inducing 80% reduction of both bacterial strains) and through the release of active ions (leading to a 54% bacterial cell count reduction for S. aureus 6538P and 30% for E. coli 8739 after 24 h). Moreover, the composite scaffolds showed high viability of MC3T3-E1 cells through both indirect and direct testing, showing promising results for their application in bone tissue engineering.
CRIS-Team Scopus Importer:2024-08-23
Keywords: 3D melt-extrusion; antibacterial; bone regeneration; hydroxyapatite; polyhydroxyalkanoates

Antibacterial Composite Materials Based on the Combination of Polyhydroxyalkanoates With Selenium and Strontium Co-substituted Hydroxyapatite for Bone Regeneration - Marcello, Elena; Maqbool, Muhammad; Nigmatullin, Rinat; Cresswell, Mark; Jackson, Philip R.; Basnett, Pooja; Knowles, Jonathan C.; Boccaccini, Aldo R.; Roy, Ipsita (Frontiers in Bioengineering and Biotechnology, 2021)
Due to the threat posed by the rapid growth in the resistance of microbial species to antibiotics, there is an urgent need to develop novel materials for biomedical applications capable of providing antibacterial properties without the use of such drugs. Bone healing represents one of the applications with the highest risk of postoperative infections, with potential serious complications in case of bacterial contaminations. Therefore, tissue engineering approaches aiming at the regeneration of bone tissue should be based on the use of materials possessing antibacterial properties alongside with biological and functional characteristics. In this study, we investigated the combination of polyhydroxyalkanoates (PHAs) with a novel antimicrobial hydroxyapatite (HA) containing selenium and strontium. Strontium was chosen for its well-known osteoinductive properties, while selenium is an emerging element investigated for its multi-functional activity as an antimicrobial and anticancer agent. Successful incorporation of such ions in the HA structure was obtained. Antibacterial activity against Staphylococcus aureus 6538P and Escherichia coli 8739 was confirmed for co-substituted HA in the powder form. Polymer-matrix composites based on two types of PHAs, P(3HB) and P(3HO-co-3HD-co-3HDD), were prepared by the incorporation of the developed antibacterial HA. An in-depth characterization of the composite materials was conducted to evaluate the effect of the filler on the physicochemical, thermal, and mechanical properties of the films. In vitro antibacterial testing showed that the composite samples induce a high reduction of the number of S. aureus 6538P and E. coli 8739 bacterial cells cultured on the surface of the materials. The films are also capable of releasing active ions which inhibited the growth of both Gram-positive and Gram-negative bacteria.
CRIS-Team Scopus Importer:2021-05-07
Keywords: antibacterial; composites; hydroxyapatite; polyhydroxyalkanoates; selenium; strontium

Electrophoretic deposition of lawsone loaded bioactive glass (BG)/chitosan composite on polyetheretherketone (PEEK)/BG layers as antibacterial and bioactive coating. - Ur Rehman, Muhammad Atiq; Bastan, Fatih Erdem; Nawaz, Qaisar; Goldmann, Wolfgang; Maqbool, Muhammad; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2018)
In this study, chitosan/bioactive glass (BG)/lawsone coatings were deposited by electrophoretic deposition (EPD) on polyetheretherketone (PEEK)/BG layers (previously deposited by EPD on 316-L stainless steel) to produce bioactive and antibacterial coatings. First, the EPD of chitosan/BG/lawsone was optimized on stainless steel in terms of suspension stability, homogeneity and thickness of coatings. Subsequently, the optimized EPD parameters were used to produce bioresorbable chitosan/bioactive glass (BG)/lawsone coatings on PEEK/BG layers. The produced layered coatings were characterized in terms of composition, microstructure, corrosion resistance, in vitro bioactivity, drug release kinetics and antibacterial activity. Ultraviolet/Visible (UV/VIS) spectroscopic analyses confirmed the release of lawsone from the coatings. Moreover, the deposition of chitosan/BG coatings was confirmed by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR). The coated specimens presented higher corrosion resistance (10 times) in comparison to that of bare 316-L stainless steel and showed convenient wettability for initial protein attachment. The presence of lawsone in the top layer provided antibacterial effects against Staphylococcus carnosus. Moreover, the developed coatings formed apatite-like crystals upon immersion in simulated body fluid, indicating the possibility of achieving close interaction between the coating surface and bone. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 3111-3122, 2018.

Substituted hydroxyapatites for antibacterial applications - Maqbool, Muhammad (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)

Synthesis, characterization, antibacterial properties, and in vitro studies of selenium and strontium co-substituted hydroxyapatite - Maqbool, Muhammad; Nawaz, Qaisar; Ur Rehman, Muhammad Atiq; Cresswell, Mark; Jackson, Phil; Hurle, Katrin; Detsch, Rainer; Goldmann, Wolfgang; Shah, Asma Tufail; Boccaccini, Aldo R. (International Journal of Molecular Sciences, 2021)
In this study, as a measure to enhance the antimicrobial activity of biomaterials, the selenium ions have been substituted into hydroxyapatite (HA) at different concentration levels. To balance the potential cytotoxic effects of selenite ions (SeO32−) in HA, strontium (Sr2+) was co-substituted at the same concentration. Selenium and strontium-substituted hydroxyapatites (Se-Sr-HA) at equal molar ratios of x Se/(Se + P) and x Sr/(Sr + Ca) at (x = 0, 0.01, 0.03, 0.05, 0.1, and 0.2) were synthesized via the wet precipitation route and sintered at 900 °C. The effect of the two-ion concentration on morphology, surface charge, composition, antibacterial ability, and cell viability were studied. Xray diffraction verified the phase purity and confirmed the substitution of selenium and strontium ions. Acellular in vitro bioactivity tests revealed that Se-Sr-HA was highly bioactive compared to pure HA. Se-Sr-HA samples showed excellent antibacterial activity against both Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus carnosus) bacterial strains. In vitro cell–material interaction, using human osteosarcoma cells MG-63 studied by WST-8 assay, showed that Se-HA has a cytotoxic effect; however, the co-substitution of strontium in Se-HA offsets the negative impact of selenium and enhanced the biological properties of HA. Hence, the prepared samples are a suitable choice for antibacterial coatings and bone filler applications.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Antibacterial; Co-substituted hydroxyapatite; Cytocompatibility; Selenium; Strontium

Three-dimensional printing of hydroxyapatite - Tufail, Asma; Schmidt, Franziska; Maqbool, Muhammad (Handbook of Ionic Substituted Hydroxyapatites, 2020)
CRIS-Team WoS Importer:2020-08-14

Tri-layered functionally graded membrane for potential application in periodontal regeneration - Shah, Asma Tufail; Zahid, Saba; Ikram, Fakhera; Maqbool, Muhammad; Chaudhry, Aqif Anwar; Rahim, Muhammad Imran; Schmidt, Franziska; Goerke, Oliver; Khan, Abdul Samad; Rehman, Ihtesham ur (Materials Science and Engineering C, 2019)
A novel tri-layered, functionally-graded chitosan membrane (FGM) with bioactive glass gradient (50%, 25%, and 0% wt.) was developed by lyophilization. A step-wise grading of chitosan, bioactive glass (BG), and Pluronic F127 was introduced into the membrane in which each layer has separate surface functions that play a role of guided tissue regeneration (GTR) membranes. The lower layer was designed to replicate alveolar bone and contains 50%wt. BG, the middle layer contains 25%wt. BG, while the upper layer was non-porous without BG and it did not support cell growth. Scanning Electron Microscopy (SEM) revealed that the lower FGM surface possessed a porous structure with embedded BG particles, while the upper surface was non-porous with interconnected architecture. The contact angle measurement confirmed that the surface with BG was hydrophilic (≈00), while the opposite surface was hydrophobic (910 ± 3.840). Both osteoblast and fibroblast cells have maximum adhesion at contact angle <80°. Alamar blue assay revealed the biocompatibility of the MC3T3-E1 mouse pre-osteoblasts cells with these membranes in vitro. The cells attachment and proliferation was seen for lower surface, while no cells adhesion was observed for the upper layer. Additionally, the interaction of the tissue with these tri-layered membranes was also investigated in vivo. Hematoxylin and eosin staining revealed the biocompatible nature of these membranes. Altogether, these results indicated that due to the biocompatible nature of these membranes, they will be a good carrier of in vivo implantation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Animal studies; Bioactivity and biocompatibility; Functionally graded membrane; Guided tissue regeneration; MC3T3-E1; Pluronic F127